Healthy Lifestyles of University Students, According to Demographics, Nationality, and Study Specialty With Special Reference to Sport Studies - Cicchella, Antonio; Vecenane, Helena; Usca, Svetlana (Frontiers in Education, 2022)
This study compares lifestyles behaviour of Italian and Latvian university students, with special reference to sport students, to assess if there are differences for gender, age, university or study speciality. An online questionnaire (Robbins, et.al., 2011) investigating healthy lifestyle habits and 8 wellness dimensions has been compiled by 155 (43.9 % females) respondents from Italy Bologna University (all having Italian nationality) and 132 from Latvia Liepaja University and Liepaja branch of Riga Stradins University (76.5 % females, all having Latvian nationality), the questionnaire contains a total of 105 questions. The responses were collected between April and December 2020. Presence of smokers in our sample is negligible. Statistical analysis was performed with SPSS v.25. At first, Cronbach’s alpha test was performed to determine the internal consistency of the survey which gave an α =.933. The answers were assessed for normality with the Kolmogorov–Smirnov (p < .05), which suggested using the nonparametric tests. Then, Kruskal–Wallis and Mann–Whitney tests were performed. Results. On the total group, statistically significant differences are found in all Wellness dimensions regarding age, gender, study specialty and university. Physical activity was associated with healthier lifestyle choices. Sport students showed more health awareness. Geographical differences were found (eating and sleeping behaviours, alcohol awareness) as well as socio-economic differences. Female students showed being more stressed than males. Occupational Wellness increased by age. Conclusion. The present study shows statistically significant differences between students’ specializations in the area of Healthy Lifestyle Habits and in all Wellness dimensions, which indicate students' health competence; and higher statistically reliable scores are for Bologna students. The research data indicate that in general there is a negative trend observed with the increase of age, lowering the indicators of Healthy lifestyle habits and Wellness dimensions. Comparing the sample of Italian and Latvian Sports students, there are statistically significant differences between universities in overall Healthy Lifestyle and all Wellness dimensions, except for Physical wellness and Financial wellness, and no significant gender differences were found. There are statistically significant differences between age indicators only in two components of Wellness (Environment wellness, Occupational wellness). Keywords: Healthy lifestyle; sport studies; wellness